Analyzing the issues of migration and identity with special reference to the Tea Tribes (Adivasis) of Assam - Das, Sankar (International Journal of Psychosocial Rehabilitation, 2020)
Migration, a historical phenomenon, deals with several issues relating to the structures of society. The identity issue of groups living within the boundaries of a society is such an issue that has a close linkage with the process of migration, which involves both immigrants and the natives of the land. In this research paper, an analysis would be done on the issues of migration and identity in the context of the tea tribes (Adivasis) of Assam state. It will also put lights upon the demand of granting Scheduled Tribe (ST) status to this community. While migrating or moving from their previous habitat, the migrating population has to encounter several obstacles that are directly or indirectly linked with the issue of identity. As an outcome of the colonial policy of exploitation adopted by the British imperial power, plantation laborers arrived at the land of Assam. After their unfruitful experiment with the natives of the land, the British imported the Adivasis from the Central Indian States to engage them in the tea industry. Since their arrival, the issue of identity has remained the major cause of concern for this community. Unlike the other states of India, where they enjoy the status of Scheduled Tribe (ST), in Assam they are being enlisted as Other Backward Classes (OBC) and are named as Tea Tribe. Contrary to this, most of them would like to call themselves Adivasi. To maintain their ST status in Assam, they have been struggling hard by upholding the demand of granting Scheduled Tribe (ST) status under constitutional safeguard.